The Effect of Early Childhood Development Programs on Women's Labor Force Participation and Older Children's Schooling in Kenya - Lokshin, Michael M.; Glinskaya, Elena; Garcia, Marito (World Bank, Washington, DC, 2015)
About 20,000 early childhood development centers provided day care for and prepared for primary school more than 1 million children aged three to seven (roughly 20 percent of children in that age group) in Kenya in 1995. The number of child care facilities reached 23,690 by the end of 1999. The authors analyze the effect of child care costs on households' behavior in Kenya. For households with children aged three to seven, they model household demand for mothers' participation in paid work, the participation in paid work of other household members, household demand for schooling, and household demand for child care. They find that: A) A high cost for child care discourages households from using formal child care facilities and has a negative effect on mothers' participation in market work. B) The cost of child care and the level of mothers' wages affect older children's school enrollment, but these factors affect boys' and girls' schooling differently. An increase in mothers' wages increases boys' enrollment but depresses girls' enrollment. C) Higher child care costs have no significant effect on boys' schooling but significantly decrease the number of girls in school.